The interaction order - Denzin, Norman K. (Bingley, U.K. : Emerald Publishing Limited, 2019)
This volume brings together leading scholars in the area of symbolic interactionism to offer a broad discussion of issues including identity, dialogue and legitimacy. Authors move the concept of interaction order into new interpretive spaces, marking the unique contributions of symbolic interactionism to the contractions that define the postmodern social order.
Prelims -- Foundations -- The interaction order -- New interpretive studies -- Index.
Includes index.
Print version record
Keywords: Symbolic interactionism; Social psychology; Social interaction; Social Science -- Sociology -- General; The self, ego, identity, personality